Occupational choice of return migrants - Matloob Piracha (IZA World of Labor, 2015)
The occupational choice of return migrants is important to their home country. Return migrants are likely to have acquired human capital while abroad, either through formal training or by working in a more efficient labor market. The employment of these newly acquired skills in the home country can have important economic implications. Examining the choice of return migrants to engage in wage employment, self-employment, entrepreneurial activity, or to remain out of the labor market makes it possible to ascertain whether the initial migration decision benefited the home country as well as the migrants and their families.
Keywords: F22; J24; J61; 330; return migration; occupational choice; selection